The Systematic Implications of the Hijri Calendar in the Caliph Umar bin Khattab’s Period for the Present - Amajida, Shafira (Universitas Islam Negeri Mataram, 2025)
This article explains the origin of the history of the preparation of the Hijri calendar calendar system during the Caliph Umar bin Khattab. This preparation was initiated by Umar bin Khattab when he received a letter of letter sent by Abu Musa Al-Ash'ari regarding time, in this case the month and year of writing his letter. The author uses a qualitative method with a historical approach based on library research by collecting data from primary sources, namely from the book of al-Muntazham fi dating al-muluk wa al-umban and secondary sources analyzed and then verified to obey a historical event to be easily understood. In his journey to formulate a calendar, Umar bin Khattab encountered many differences of opinion among friends. The considerations made by Umar bin Khattab are not solely for personal interests, but for the interests of the people. Therefore, the systematic calendar of Hijri is a way of synifying God's religion